A relação dos valores organizacionais na implementação de um modelo de melhoria de processo de software - Bacelar, Sueli Dantas (2015)
The Information Technology (IT) market is growing. The number of companies and the volume of contracting in IT has increased. Because of the increasing competition, organizations need to improve their market presence and mainly seek increased efficiency and effectiveness through the implementation of software process improvement (SPI). Passos, Dias-Neto e Barreto (2012a) to believe that the results of this initiative appear when the achieved benefits are aligned with the organizational values. This study aims to verify the benefits achieved by organizations with the implementation of MPS.BR; to identify if organizational values are present in these organizations and to verify the existence of relationship between the benefits achieved by the implementation of software process models and organizational values. Data collection was conducted through questionnaires in organizations which implemented MPS.BR. The participants were 9 organizations, 47 questionnaires were answered. Benefits surveyed "clearer processes" and "processes with more quality" were the most perceived as "reduction in development time" and "reduction in the cost of development", the less checked by employees. After completing statistical analyzes, it was possible to reduce to four factors the 18 benefits studied, identifying the categories: quality, control, process and staff. Of the 10 organizational values studied, the most noted were "teamwork" and "responsibility" and the least observed were "strategy" and "information". The statistical analysis showed the relationship between the benefits and the organizational values, showed that organizational commitment and supervision values are strongly correlated of impactful on the benefits, suggesting that software development organizations that wish to achieve the benefits from the implementation of MPS.BR should focus their efforts on strengthening the supervision in their organization and develop a commitment to their team.